Pola Perilaku Konsumtif Mahasiswa Terhadap Penggunaan Aplikasi Belanja Online Ditinjau dari Perspektif Ekonomi Islam - Layla Novitasari; Nurti Budiyanti; Hayatin Nufus; Muhammad Ahyar; Putri Wulandari (TAFAQQUH, 2023)
This research is motivated by the existence of excessive consumptive behavior by students whose goal is only for self-satisfaction. The purpose of this study is to analyze how opinions regarding the consumer behavior of students using Online shopping applications are seen from an Islamic economic perspective. This study used a descriptive qualitative method. Data collected using data collection techniques, by means of literature studies. Data collected using data collection techniques, by means of literature studies. Judging from the data from the Central Statistics Agency (BPS), smartphone use in Indonesia grew significantly in 2019 by 89.09%, this value was greater than in 2015. From the latest data by sirclo, after the pandemic, in 2021, according to published data there are 88% of internet users who buy products Online in Indonesia. 47.4% of respondents set aside less than IDR 100,000, 50.9% of respondents set aside around IDR 100,000 - IDR 500,000 and the most consumptive 1.8% of respondents set aside IDR 600,000 - IDR 1000,000. It It can be concluded that the level of consumerism in Indonesia is quite high, judging from the data that has been studied.